Prevalence and genotype distribution of human papillomavirus infection among women: A population‐based study in Dali Bai Autonomous Prefecture, Yunnan Province, China. Issue 8 (21st April 2019) - Su, Ya; Yuan, Zhiqiong; Xu, Chunping; Li, Zhengjin; Zhu, Renjian; Zhang, Wei; Cao, Rongrong; Yan, Xuyi; Liu, Yunchun
Abstract: Accumulating evidence indicates that persistent infection with high‐risk oncogenic human papillomavirus (HPV) genotypes is the most important risk factor for cervical cancer, and that the distribution of HPV genotypes varies regionally. This study explored the prevalence and genotype distribution of HPV infection among Han, Yi, and Bai women in various regions of Dali Bai Autonomous Prefecture, Yunnan Province, China. This cross‐sectional study included 2779 women (20–76 years old) who were referred for 21‐HPV genotype array diagnostic from five regions of Dali Bai Autonomous Prefecture between February 2013 and May 2016. Statistical methods used included a the χ 2 test, Fisher's exact test, t test, and logistic regression. Overall HPV prevalence in the study population was 7.6%. HPV‐52, HPV‐58, HPV‐18, HPV‐81, and HPV‐16 were the most prevalent genotypes in the study area, and notably, the prevalence of HPV‐58 was significantly higher among women in Heqing County than that in other regions. Univariate analysis showed that husband's age, region, fertility status, and parity were potential factors associated with HPV infection. Multivariate logistic regression analysis revealed that Heqing County was an independent risk factor for HPV infection among women in the Dali area, moreover, Yi women showed the highest risk for HPV infections. Overall, our finding emphasizing the urgent need for an HPV screening and prevention program in Heqing County and Yi women. We also suggest that HPV‐related health education should be provided not only to women, but also to men, to reduce the risk of infection in women. Highlight: The HPV prevalence was 7.6% among Han, Yi, and Bai women in various regions of Dali Bai Autonomous Prefecture, Yunnan Province, China. HPV‐52, HPV‐58, HPV‐18, HPV‐81, and HPV‐16 were the most prevalent genotypes in the study area. Heqing County was an independent risk factor for HPV infection among women in the Dali area, and the prevalence of HPV‐58 was significantly higher among women in Heqing County than that in other regions. Yi women showed the highest risk for HPV infections.